2021
DOI: 10.1042/bcj20210155
|View full text |Cite
|
Sign up to set email alerts
|

FATP4 inactivation in cultured macrophages attenuates M1- and ER stress-induced cytokine release via a metabolic shift towards triacylglycerides

Abstract: Fatty acid transport protein 4 (FATP4) belongs to a family of acyl-CoA synthetases which activate long-chain fatty acids into acyl-CoAs subsequently used in specific metabolic pathways. Patients with FATP4 mutations and Fatp4-null mice show thick desquamating skin and other complications, however, FATP4 role on macrophage functions has not been studied. We here determined whether the levels of macrophage glycerophospholipids, sphingolipids including ceramides, triacylglycerides, and cytokine release could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…However, the relationship between TAM and tumor remains to be clarified: (1) With the development of studies in mononuclear phagocyte lineage, the mechanism of proliferation needs to be reexamined, especially source and maintenance levels of macrophages in human cancers. (2) The integrity of the tumor and the surrounding environment and heterogeneity and subject characteristics, all cells in the environment of in situ research are particularly important in time and space. Different space should be more widely studied to observe the change in the cells during different stages with the overall objective of examining the occurrence of tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between TAM and tumor remains to be clarified: (1) With the development of studies in mononuclear phagocyte lineage, the mechanism of proliferation needs to be reexamined, especially source and maintenance levels of macrophages in human cancers. (2) The integrity of the tumor and the surrounding environment and heterogeneity and subject characteristics, all cells in the environment of in situ research are particularly important in time and space. Different space should be more widely studied to observe the change in the cells during different stages with the overall objective of examining the occurrence of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that there is connection with energy regulation, immune surveillance and vital organ functions. Cancer changes the relationship with the immune state in various ways, such as the production of certain cytokines ( 2 ), antigen presentation ( 3 ), the immune response ( 4 ), checkpoint expression ( 5 ), and immune exhaustion ( 6 ). The function of immune cells depends on the normal process of nutrient metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids from BMDMs were extracted by using hexane:isopropanol (3:2 vol/vol) containing internal standards according to our published procedure ( 22 ). The profile of 164 phospholipids (PLs) and sphingolipids (SPLs) was obtained by liquid-chromatography mass spectrometry (LC-MS/MS) with running conditions described previously ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lipids from BMDMs were extracted by using hexane:isopropanol (3:2 vol/vol) containing internal standards according to our published procedure ( 22 ). The profile of 164 phospholipids (PLs) and sphingolipids (SPLs) was obtained by liquid-chromatography mass spectrometry (LC-MS/MS) with running conditions described previously ( 22 ). Internal standards were phosphatidylcholine (PC)-17:0/17:0, phosphatidylethanolamine (PE)-12:0/12:0, phosphatidylserine (PS)-17:0/17:0, phosphatidylinositol (PI)-17:0/17:0, and Cer-17:0 (Avanti Polar Lipids, Alabaster, AL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation